Legacy Effects in Radical Innovation: A Study of European Internet Banking - Erik H. Schlie; Jaideep C. Prabhu; Rajesh K. Chandy (European School of Management and Technology (ESMT), 2008)
How do firms cope with the challenges of disruptive change in their industry? Numerous studies have highlighted that success with any prior technology creates a negative legacy effect for the next radical technological shift. We question the overly pessimistic view of such legacy effects and ask how quickly firms embrace technological breakthroughs by radically innovating and who wins in the longer term? In this paper, we argue that legacy is a multi-faceted construct whose diverse aspects could simultaneously have different effects on innovation speed and market performance. We identify three main types of legacy related to technology, organizational, and country-level influences. Previous research tends to focus on technological or market effects in isolation, whereas we seek to study the effects of both firm and country legacy simultaneously on speed to radical innovation and market performance over time. Based on a conceptual framework we develop six hypotheses concerning the legacy effects on initial speed radical innovation and subsequent market performance. We chose the European retail banking industry and the focal innovation of transactional Internet banking as a suitable empirical context to employ quantitative hypothesis testing. Detailed and longitudinal (1996-2001) data were collected for a sample of 123 banks from six European countries: United Kingdom, Germany, France, Sweden, Finland, and Denmark. We specified a model and used threestage least squares (3SLS) as a method to estimate simultaneous regression equations due to endogeneity of a key variable. We show that the prevailing negative view of legacies is likely to be overstated.
urn:nbn:de:101:1-201106143453
Keywords: M31; 650; innovation; legacy; internet banking; europe